Analysis of the Relationship between Service Quality, Patient Satisfaction, Patient Trust, and Patient Loyalty at Primary Health Centre - Saniyya Syarif Hamdoen; Burhanudin Burhanudin; Basuki Rachmat (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to empirically examine the influence of service quality on patient loyalty, with patient satisfaction and patient trust acting as mediating variables. The research was conducted at Sawah Pulo Health Centre in Surabaya, Indonesia. A total of 224 respondents participated in this study through purposive sampling. The data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that service quality significantly influences patient satisfaction and trust. Furthermore, trust emerged as the strongest predictor of loyalty, and both satisfaction and trust mediate the relationship between service quality and loyalty. These findings imply that enhancing service quality, alongside building patient satisfaction and trust, is essential for fostering long-term patient loyalty in primary healthcare settings.